2021
DOI: 10.1007/s12551-021-00837-2
|View full text |Cite
|
Sign up to set email alerts
|

Tools for studying and modulating (cardiac muscle) cell mechanics and mechanosensing across the scales

Abstract: Cardiomyocytes generate force for the contraction of the heart to pump blood into the lungs and body. At the same time, they are exquisitely tuned to the mechanical environment and react to e.g. changes in cell and extracellular matrix stiffness or altered stretching due to reduced ejection fraction in heart disease, by adapting their cytoskeleton, force generation and cell mechanics. Both mechanical sensing and cell mechanical adaptations are multiscale processes. Receptor interactions with the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 106 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…The applicability of equations (3,4) and (15,16) to both AT and BT cut crystals was experimentally verified in both Newtonian sucrose solutions and non-Newtonian (viscoelastic) PEG 2000 solutions at different concentrations (Figure S1). with the largest storage and loss moduli, obeying the cellular tensegrity model.…”
Section: Because the Decay Length Of The Thickness Shear Wave Of Quar...mentioning
confidence: 88%
See 2 more Smart Citations
“…The applicability of equations (3,4) and (15,16) to both AT and BT cut crystals was experimentally verified in both Newtonian sucrose solutions and non-Newtonian (viscoelastic) PEG 2000 solutions at different concentrations (Figure S1). with the largest storage and loss moduli, obeying the cellular tensegrity model.…”
Section: Because the Decay Length Of The Thickness Shear Wave Of Quar...mentioning
confidence: 88%
“…The Sauerbery equation 1 and the above theoretical relations between the measured changes in frequency, motional resistance or bandwidth and the liquid's viscosity, viscoelasticity were derived for AT-cut quartz crystals, however, it was theoretically predicted that equations ( 1) and ( 3) can be extended to other pure shear mode cuts including BT-cut but with some different response slopes owing to their difference in shear modulus, [18] shear wave velocity or acoustic impedance. Here we further assume that equations (4)(5)(6) can also be applied to other pure shear mode cuts including BT-cut.…”
Section: Theoretical Background and Equations For Drpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Arteries are composite structures, with mechanical properties that differ between micro-and macroscale, and direction of strain. Generally, microscale stiffnesses are magnitudes lower compared to the macroscale (23,24), which is a result of the specific mechanical behavior at different length scales, as well as sample preparation and measurement techniques (25). At the microscale, comparative studies between the individual arterial wall layers suggested that the intima was more compliant compared to the media layer (26) and studies report values that ranged from 5 to 50 kPa (26,27) and ~30 to 190 kPa (28)(29)(30) in the intima and media layers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular and subcellular mechanics can be studied using optical tweezers [16][17][18]. The various techniques used to probe cell mechanics have been reviewed in detail elsewhere [19,20]. In spite of this wide range of tools, simultaneous measurements of passive and active single cardiomyocyte mechanics in axial and radial directions have not been reported.…”
Section: Introductionmentioning
confidence: 99%